Pregnancy-associated Cancers: A Narrative Review (Epidemiology, Biostatistics, and Public Health, 2024)
Pregnancy-associated cancers are malignancies diagnosed during pregnancy or within one year of delivery or abortion. These cancers present unique challenges because of the delicate balance required for maternal-fetal health. Diagnosis can be made complex by physiological changes associated with pregnancy, and treatment decisions must take into account potential harm to the foetus. Multidisciplinary collaboration between oncologists and obstetricians is essential. Despite the complexities, early detection and tailored management can optimise outcomes for both mother and child. A systematic approach is currently lacking; further research into prenatal exposure to maternal cancer is recommended to formulate evidence-based guidelines for the management of cancer in pregnancy.
Keywords: cancer; chemotherapy; pregnancy